2014
DOI: 10.1523/jneurosci.5407-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Memory Accuracy by Left Prefrontal Transcranial Direct Current Stimulation

Abstract: Human memory is dynamic and flexible but is also susceptible to distortions arising from adaptive as well as pathological processes. Both accurate and false memory formation require executive control that is critically mediated by the left prefrontal cortex (PFC). Transcranial direct current stimulation (tDCS) enables noninvasive modulation of cortical activity and associated behavior. The present study reports that tDCS applied to the left dorsolateral PFC (dlPFC) shaped accuracy of episodic memory via polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 38 publications
(10 reference statements)
5
63
0
Order By: Relevance
“…Hence, effects of stimulation may differ depending on when it is applied (Brunoni et al, 2012;Hill et al, 2016). A study comparing delayed recognition of new and old pictures, with anodal tDCS applied over the left PFC during encoding, showed a decrease in performance (Zwissler et al, 2014) -a result similar to our study.…”
Section: Verbalsupporting
confidence: 86%
See 1 more Smart Citation
“…Hence, effects of stimulation may differ depending on when it is applied (Brunoni et al, 2012;Hill et al, 2016). A study comparing delayed recognition of new and old pictures, with anodal tDCS applied over the left PFC during encoding, showed a decrease in performance (Zwissler et al, 2014) -a result similar to our study.…”
Section: Verbalsupporting
confidence: 86%
“…However, recent studies also report a drop in performance following anodal tDCS (Ferrucci et al, 2008;Jones and Berryhill, 2012;Kaminski et al, 2013;Zwissler et al, 2014;Schaal et al, 2015) or improvements following cathodal tDCS (Smirni et al, 2015). A recent tDCS study reported a significant decrease in performance in an old/new recognition task following anodal tDCS over the left PFC during encoding of pictures (Zwissler et al, 2014). Ferrucci et al (2008) reported a detrimental effect of anodal tDCS stimulation over the PFC during a task assessing working memory.…”
Section: Verbalmentioning
confidence: 99%
“…Via pFC-parietal intercommunication, the observed stimulation effect could also partly draw on parietal representations, for instance in form of an enhanced number fact retrieval from relevant parietal sites (Smirni, Turriziani, Mangano, Cipolotti, & Oliveri, 2015;Klein, Moeller, Glauche, Weiller, & Willmes, 2013;Dehaene et al, 2003). As for the latter, cathodal stimulation has been attributed a noise filter function before (Miniussi, Harris, & Ruzzoli, 2013) that allowed more effective distinctions between target and flanker or lure stimuli (Zwissler et al, 2014;Weiss, Lavidor, O'Neil, & Adamson, 2012). Seeing the flexible emergence of SNARC also observed from different context manipulations (Fischer, Mills, & Shaki, 2010;Bächtold, Baumüller, & Brugger, 1998), slight membrane threshold modulations by tDCS might have just blocked the jittery and task-irrelevant spatial-numerical signal chain.…”
Section: Discussionmentioning
confidence: 99%
“…(A) Participants judged colors (Simon task) and digit parity (Experiments 1 and 3) or digit magnitude (Experiment 2; SNARC tasks) by index finger key presses. (B) The active tDCS electrode (cathode) was placed over the left pFC (F3), and the reference electrode (anode) was placed on the contralateral upper arm to avoid an opposite polarization of another cortical region(Zwissler et al, 2014;Wolkenstein & Plewnia, 2013). Electrode positions were interchanged for Experiment 3.…”
mentioning
confidence: 99%
“…A combination of behavioral training and non-invasive brain stimulation was also shown to present a new adjuvant in the treatment of neurological patients after brain injury (Wessel et al 2015). Using transcrancial direct current stimulation (tDCS), it could recently be demonstrated that episodic memory retrieval is dependent from activity during the encoding phase (Zwissler et al 2014) and that cognitive training of working memory is superior if applied ''online'' (tDCS during performance) in contrast to priming (tDCS before performance) (Martin et al 2014). These findings and our preliminary data highlight the role of state-dependent effects of non-invasive brain stimulation and opens new research questions dealing with the exact combination schemes of therapeutic interventions and noninvasive brain stimulation.…”
Section: Perspectivesmentioning
confidence: 99%